REMOVAL OF DYES IN SONGKET WASTE WATER BY USING PHOTOCATALYST Chitosan-TiO2 - Oktarina, Kurniawati - (Universitas Muhammadiyah Palembang, 2019)
Photocatalyst is one of the catalysts that works when given a certain light and generally is a semiconductor that has a full valence band and an empty conduction band, such as TiO2. Synthesis of chitosan-TiO2 nanocomposite research has been carried out, nanocomposites produced from squid cartilage as chitosan-?. Nanocomposites are synthesized by combining chitosan as a supporting material and TiO2 which has a function as a high photocatalytic. Characterization of chitosan-TiO2 nanocomposites by FTIR and SEM / EDX which shows the functional groups and surface morphology of the nanocomposite. FTIR analysis shows the absorption band of O-Ti-O in the region of 678.98 cm-1 and the typical absorption of chitosan at wave numbers –OH 3425.58 cm 1, 3834.49 cm-1, and 3873.06 cm-1. From SEM / EDX analysis it can be seen that TiO2 is evenly distributed on the surface of chitosan. Then nanocomposite was applied with wrna procion in Palembang songket liquid waste. Chitosan-TiO2 nanocomposites from squid cartilage were able to degrade procion dyes in water medium with the help of UV light at the optimum wavelength of 520 nm, where the percentage of photodegradation was 54.47%. Which nanocomposite is also able to reduce the concentration of procion dyes from 5 mg / L to 1.9 mg / L with an initial acidity (pH) of 10.34 to 7.13. Key words: Photocatalyst, nanocomposites, Procion Red